Evaluation of oral health education programs among patients with schizophrenia in India: An interventional study - Binu Purushothaman; Karishma; Akriti Agrawal; Jazib Nazeer; Basanta K. Choudhury; Jagadish Prasad Rajguru; Irfanula Huda; Indrani Das (Wolters Kluwer Medknow Publications, 2024)
BACKGROUND: Schizophrenia is a mental disease that can drastically affect oral health. Hence, this remains a significant factor that affects oral health-related quality of life (OHRQoL). Assessing the OHRQoLin schizophrenic patients is one of the primary needs. The oral health impact profile is an impressive range of instruments that assesses the impact of oral conditions on well-being and quality of life. MATERIALS AND METHODS: A 100 schizophrenic individuals were randomly selected from the Psychiatry Department of Government Hospital, Patna, Bihar, India, and grouped into two groups: (a) Group I with.group-based sessions and (b) Group II with one-on-one interactions. Inclusion criteria: (a) Individuals who received the clinical confirmatory diagnosis of schizophrenia, (b) Patients who regularly reported to the psychologist for periodic evaluation, and (c) Patients who could follow instructions. Exclusion criteria: (a) Patients or their caregivers who were unwilling to participate in the study, (b) Patients with any other mental health disability other than schizophrenia, (c) Patients with muscular or nervous system disorders, and (d) Patients who could not follow instructions. Patients were educated on the modified Bass technique, and mean ± standard deviation plaque scores were compared at the baseline and after 12 weeks of intervention. RESULTS: Statistical analysis was performed using the Chi-square analytical test and paired "t-test." Statistically significant differences were observed in plaque scores in both groups (P < 0.001). CONCLUSION: Educational training tools help in improving oral health in schizophrenic patients.